Match Report Application for Match Commissioner (MC) Football Match - Nurkadri Nurkadri; Argubi Silwan; Indra Darma Sitepu; Mawardi Nur; Taufik Akbar; Rizky Nursasongko Gunri (UNIB Press, 2021)
This study aims to develop an application to report the results of Match Commissioner (MC) ASKOT PSSI Medan. Furthermore, this application is to improve the human resources of ASKOT PSSI Medan specifically for match equipment, namely MC. This research method is the development research of Budiono Saputro which adopts Borg & Gall and Sukmadinata, then this research uses 2 (two) stages, namely stage 1 literature study, conducting literature review and needs analysis (needs questionnaire), then designing a product model and stage 2 developing and planning models do make applications, expert validation and revisions, individual trials and revisions, and group trials. The MC assessment of the application of the MC report results in the display aspect was 84.81% in the very good category, in the content / material aspect of 86.53% it was in the very good category, in the usage aspect it was 85.46% in the very category. good, and in the overall aspect of 85.76% it is in the very good category. It is concluded that the MC report application based on the assessment data of the MC ASKOT PSSI Medan city of the application developed is suitable for use with improvements according to suggestions and input, then used as the final product of this study.